Preschool Enrollment, Classroom Instruction, Elementary School Context, and the Reading Achievement of Children from Low-Income Families - Crosnoe, Robert (Res Sociol Educ, 2016)
PURPOSE: The goal of this study was test expectations derived from sociological and developmental perspectives that the association between phonics instruction in kindergarten classrooms and reading achievement during the first year of school in the low-income population would depend on whether children had previously attended preschool as well as the socioeconomic composition of their elementary schools. METHODOLOGICAL APPROACH: Autoregressive modeling was applied to nationally representative data from 7,710 children from low-income families in the Early Childhood Longitudinal Study-Kindergarten Cohort, with a series of sensitivity tests to improve causal inference and explore the robustness of results. FINDINGS: The association between phonics instruction and achievement was strongest among children from low-income families who had not attended preschool and then enrolled in socioeconomically disadvantaged elementary schools and among children from low-income families who had attended preschool and then enrolled in socioeconomically advantaged elementary schools. RESEARCH AND PRACTICAL IMPLICATIONS: Insight into educational inequality can be gained by situating developing children within their proximate ecologies and institutional settings, especially looking to the match between children and their contexts. These findings are relevant to policy discussions of early education, instructional practices, and desegregation.